Isolation, purification and structural characterization of polysaccharide from Acanthopanax brachypus. (20th August 2015) - Hu, Haobin; Liang, Haipeng; Wu, Yun
Highlights: A new polysaccharide (ABPS-21) from the stem barks of Acanthopanax brachypus was isolated and purified. The structure of ABPS-21 was established by chemical methods and NMR spectroscopy. ABPS-21 consists mainly of galactose, glucose, rhamnose and galacturonic acid. ABPS-21 was a new acidic branched polysacchride. Abstract: A water-soluble polysaccharide, designated as ABPS-21, was isolated from the stem barks of Acanthopanax brachypus by hot-water extraction and purified by Cellulose DEAE-52 and Sephacryl S-300 HR gel-filtration chromatography, respectively. The homogeneity and molecular weight were determined using HPGPC. The structure was elucidated based on monosaccharide composition and methylation analysis, partial acid hydrolysis, periodate oxidation, Smith degradation, IR and NMR spectroscopy. The result showed that ABPS-21 was a homogeneous heteropolysaccharide including galactose, glucose, rhamnose and galacturonic acid in a molar ratio of 3.0:2.0:2.0:1.0, respectively, with an average molecular weight of 1.06 × 10 5 Da. The main chain of ABPS-21 was made up of →4)-β-d -Gal p -(1→4)-β-d -Glc p -(1→4)-β-d -Gal p -(1→4)-β-d -Gal p -(1→2)-α-l -Rha p -(1→, and two side chains α-l -Rha p -(1→4)-β-d -Glc p -(1→ and α-d -gal p A-(1→ were attached to the backbone chain at O -6 position of 1, 4, 6-linked β-d -Glc p and 1, 4, 6-linked β-d -Gal p, respectively. ABPS-21, an acidic branched polysaccharide from A. brachypus, was not described up to now.